1997
DOI: 10.1021/np970034t
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Novel Antimicrobial Fatty Acid (5Z,9Z)-14-Methyl-5,9-pentadecadienoic Acid in Eunicea succinea

Abstract: The phospholipid fatty acid composition of Eunicea succinea was investigated, and the novel (5Z,9Z)-14-methyl-5,9-pentadecadienoic acid was identified. Structural characterization was accomplished by means of mass spectrometry of its pyrrolidide derivative, NMR, FT1R, and total synthesis. Other interesting phospholipid fatty acids in E. succinea were the tetracosapolyenoic acids 6,9,12,15,18,21-tetracosahexaenoic acid (24:6) and 6,9,12,15,18-tetracosapentaenoic acids (24:5). The title compound was particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 12 publications
0
19
0
1
Order By: Relevance
“…The presence of two methyl groups was revealed by the signals at δ 22.6 in the 13 C NMR spectrum (C-24, C-25) and at δ 0.86 in the 1 H NMR spectrum (d, J = 6.6 Hz, an isopropyl group). The signal at δ 39.1 (C-22) in the 13 C NMR spectrum confirmed the position of methyl branching at C-23 (20,21). Mass spectrum of the tetrahydropyrrolidide (2e) obtained from 2a exhibited a molecular ion peak at m/z 435 (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…The presence of two methyl groups was revealed by the signals at δ 22.6 in the 13 C NMR spectrum (C-24, C-25) and at δ 0.86 in the 1 H NMR spectrum (d, J = 6.6 Hz, an isopropyl group). The signal at δ 39.1 (C-22) in the 13 C NMR spectrum confirmed the position of methyl branching at C-23 (20,21). Mass spectrum of the tetrahydropyrrolidide (2e) obtained from 2a exhibited a molecular ion peak at m/z 435 (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…Depuis le milieu des années 1990, le domaine d'existence des AG Δ5,9 s'est progressivement étendu aux anémones de mer (Carballeira et Medina, 1994b ;Carballeira et Reyes, 1995) et aux zoanthides, avec en particulier l'identification du nouveau 6-bromo-5,9-eicosadiè-noïque (Carballeira et Reyes, 1995), aux gorgones (Carballeira et al, 1997b), aux mollusques (Kawashima et Onishi, 2004, aux nudibranches (Zhukova, 2007). Les AG non maloniques les plus fréquents chez les mollusques (20:2 Δ5,13 ou 22:2 Δ7,15 par exemple) sont également souvent présents dans ces dernières compositions.…”
Section: Ag Non Maloniques D'autres Organismesunclassified
“…( Lam et al, 1989), Petrosia sp. (Carballeira et Shalabi, 1993 ;Carballeira, 1997b), Xestospongia sp. (Li et al, 1995), Cinachyrella aff.…”
Section: Ag Bromésmentioning
confidence: 99%
“…Fatty acids with D 5,9 -position of two double bonds are mostly present in marine sponges (Carballeira and Shalabi, 1990;Carballeira and Maldonado, 1986), and in some marine invertebrates, e.g. sea anemone Stoichactis helianthus (Carballeira and Medina, 1994), or sea rod Eunicea succinea (Carballeira et al, 1997) but in myxomycetes they were identified for the first time. The antimicrobial activity of some D 5,9 -acids was also described (Carballeira et al, 1997).…”
Section: Lipidsmentioning
confidence: 99%
“…sea anemone Stoichactis helianthus (Carballeira and Medina, 1994), or sea rod Eunicea succinea (Carballeira et al, 1997) but in myxomycetes they were identified for the first time. The antimicrobial activity of some D 5,9 -acids was also described (Carballeira et al, 1997).…”
Section: Lipidsmentioning
confidence: 99%